2020
DOI: 10.3390/biom10050667
|View full text |Cite
|
Sign up to set email alerts
|

Mining Drug-Target Associations in Cancer: Analysis of Gene Expression and Drug Activity Correlations

Abstract: Cancer is a complex disease affecting millions of people worldwide, with over a hundred clinically approved drugs available. In order to improve therapy, treatment, and response, it is essential to draw better maps of the targets of cancer drugs and possible side interactors. This study presents a large-scale screening method to find associations of cancer drugs with human genes. The analysis is focused on the current collection of Food and Drug Administration (FDA)-approved drugs (which includes about one hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Following this line of research, artificial intelligence (AI) and machine learning (ML) methods have been proven to be also very useful for integrating large-scale- omics data from cancer patients and for analyzing gene expression profiles in response to different drugs [ 231 ]. In this scenario, positive associations between gene expression and anticancer drug activity allowed the discovery of gene targets for the drugs tested [ 232 ]. Conversely, a negative association between gene expression and drug activity measured in these assays (for example, detecting high expression of a gene corresponding to decreased activity of a drug) indicated that such a gene/protein could be mediating resistance and low sensitivity to the drug.…”
Section: Methodologies To Access Tki Resistancementioning
confidence: 99%
“…Following this line of research, artificial intelligence (AI) and machine learning (ML) methods have been proven to be also very useful for integrating large-scale- omics data from cancer patients and for analyzing gene expression profiles in response to different drugs [ 231 ]. In this scenario, positive associations between gene expression and anticancer drug activity allowed the discovery of gene targets for the drugs tested [ 232 ]. Conversely, a negative association between gene expression and drug activity measured in these assays (for example, detecting high expression of a gene corresponding to decreased activity of a drug) indicated that such a gene/protein could be mediating resistance and low sensitivity to the drug.…”
Section: Methodologies To Access Tki Resistancementioning
confidence: 99%
“…Genome and proteome-wide information associated to the drugs activity in human cells is essential to generate better maps of the molecular targets of each drug (De Las Rivas et al 2018 ). Construction of this type of drug-target interaction mapping has been successful in the field of cancer genomics thanks to the possibility of testing the activity of hundreds of cancer drugs in multiple human cancer cell lines (Arroyo et al 2020 ). Similar studies using genomic data combined with drugs activity are needed to elucidate at molecular level the genetic and somatic basis for inter-individual differences in drug response.…”
Section: Bioinformatic Investigation In Drug Resistance and In Emtmentioning
confidence: 99%
“…Every year, more than 10 million new cancer cases and nearly seven million deaths are reported worldwide [ 1 ]. Chemotherapy is one of the most widely used modalities for cancer treatment, with over one hundred clinically approved drugs available [ 2 ]. Among them, camptothecin (CPT) [ 1 ] (1, Figure 1 ), a quinoline alkaloid as an inhibitor of topoisomerase I, is a well-known drug isolated from the Chinese tree Camptotheca by Wall et al in 1966 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%